Adolescentes em editoriais da revista Capricho: linguagem, contexto e representação - Olmos, Olívia Martins de Quadros (2011)
This paper aims to analyze how language is used to show representations on adolescence in editorials of Capricho magazine. To do so, we use pressupositions of Systemic-Functional Linguistics concerning interpersonal and ideational (experiential) metafunctions. The corpus is composed of 24 editorials published in Capricho from January to December, 2009. Having as basis aspects of the Mood and transitivity systems (HALLIDAY & MATTHIESSEN, 2004) and of Appraisal Theory (MARTIN & WHITE, 2005), the steps followed are: a) identification of the recurrent terms adolescent and adolescence as well as their referrers (pronouns, synonyms, ellipses); b) identification of speech functions and clause moods; c) quantification and analysis of the occurrence of appraisal in terms of attitude (affect, judgment and appreciation) and gradation (force and focus) in clauses with reference to adolescents; d) description and analysis of the components of transitivity in clauses that constitute the text in order to verify the lexico-grammatical roles developed by the adolescent girls. In relation to the interpersonal resources, the analysis showed the use of explicit commands and of interpersonal metaphors as interaction resources with the female readers. The most frequent appraisal categories in the corpus are judgment, denoting relationship evaluation (dating, family and friendship), leisure (vacations and parties) and study (school, courses and exchange study), characterizing contexts in which the adolescent girls are socially inserted. From the analysis of the resources of transitivity, we find that the adolescent is represented, in the texts analyzed, as a girl who dates who walks, who loves the holidays, going to shows and events that relate to family and friends.